Asinine milk mitigates stress-mediated immune, cortisol and behavioral responses of piglets to weaning: A study to foster future interventions in humans - Farias, Sharacely de Souza; Dierings, Ana Carolina; Mufalo, Vinicius Cardoso; Sabei, Leandro; Parada Sarmiento, Marisol; Silva, Arthur Nery da; Ferraz, Priscila Assis; Pugliesi, Guilherme; Ribeiro, Claudio Vaz Di Mambro; Oliveira, Chiara Albano de Araujo; Zanella, Adroaldo José (Frontiers in Immunology, 2023)
This study assessed whether asinine milk supplementation improved the immune and behavioral responses of piglets during an early life weaning stress event as a model for its future use in humans. Were used 48 piglets from 4 different litters. At 20 days of age, piglets were weighed and allocated with their litter and dam into group pens until 28 days of age. Four piglets from each litter were randomly assigned to either (1) asinine milk supplementation, (2) skimmed cow milk supplementation or (3) no supplementation (control group). The supplementations were voluntarily administered for 3 days pre and postweaning. The effects on the weaning stress response were assessed through salivary cortisol measurements; behavioral tests such as the open field, novel object end elevated plus maze tests; and gene expression of HSD11B1, NR3C1 and IL1B in PBMCs and normalized to GAPDH and UBB. A randomized block design was used to test the effect of the supplementations on weight-milk intake-gene expression-behavior. The effects on salivary cortisol were determined using the ratio between the morning/afternoon concentrations. Principal component analysis and Fisher’s test were performed to evaluate the behavior test data. When comparing salivary cortisol concentrations between the pre- and postweaning periods, there was a difference (p<0.05) between the supplementation groups in the afternoon period, suggesting that piglets fed asinine milk had lower afternoon cortisol concentrations postweaning than their counterparts. For the behavioral tests, the supplementations had no measurable effects. No difference was found between groups pre- and postweaning for the expression of HSD11B2, which codes for an enzyme that breaks down cortisol. However, the expression of NR3C1, which encodes the glucocorticoid receptor, was significantly upregulated in piglets supplemented with cow milk (mean=1.245; p=0.04; mean=8.11; p=0.049). Asinine milk downregulated 1L1B gene expression, which codes for an inflammatory cytokine. In conclusion, these results suggest that supplementation with asinine milk may represent a strategy to diminish the damage associated with an early life event by modulating IL1B expression and reducing salivary cortisol levels in piglets undergoing weaning stress. Further transcriptomic and metabolomic studies may improve our understanding of the molecular pathways that mediate this systemic immune-mediated response.